2014
DOI: 10.1002/etc.2466
|View full text |Cite
|
Sign up to set email alerts
|

Biological responses of marine flatfish exposed to municipal wastewater effluent

Abstract: There is increasing concern over the presence of pharmaceutical compounds, personal care products, and other chemicals collectively known as contaminants of emerging concern (CECs) in municipal effluents, yet knowledge of potential environmental impacts related to these compounds is still limited. The present study used laboratory exposures to examine estrogenic, androgenic, and thyroid-related endocrine responses in marine hornyhead turbot (Pleuronichthys verticalis) exposed to CECs from municipal effluents w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…1). The level of wastewater treatment among the POTWs discharging at the outfall locations varies from advanced primary to full secondary 7, 12. Discharge flow capacity for each of these outfalls range between 170 and 350 million gallons per day for a sum total exceeding 1 billion gallons per day.…”
Section: Methodsmentioning
confidence: 99%
“…1). The level of wastewater treatment among the POTWs discharging at the outfall locations varies from advanced primary to full secondary 7, 12. Discharge flow capacity for each of these outfalls range between 170 and 350 million gallons per day for a sum total exceeding 1 billion gallons per day.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of contaminant levels in sediments at the site of collection and in fish tissues would also provide additional valuable information on exposure, but does not diminish the importance of field data on biological responses, which account for factors affecting bioavailability as well as the possibility of detecting responses from rapidly metabolized compounds such as PAHs, and many estrogenic contaminants such as hormones and hormone mimics. Also, several laboratory studies evaluating exposure to sewage effluents have not shown these biomarkers to link directly to dose (Vidal-Dorsch et al, 2014). Further work will be needed to evaluate what combinations of environment factors (chemical exposure, temperature, hypoxia) may be contributing to the patterns in CYP1A and VTG expression we observed in juvenile flounder.…”
Section: Measures Of Exposure To Environmental Contaminantsmentioning
confidence: 81%
“…All of the exogenous estrogens have the potential to mimic naturally occurring 17β‐estradiol and exert their action in low concentrations, resulting in alterations of absolute and relative concentrations of sex steroids in circulation and in tissues (Hecker et al ). For example, exposure of the marine hornyhead turbot ( Pleuronichthys verticalis ) to estradiol caused significant reduction in 11‐ketotestosterone (Vidal‐Dorsch et al ). Reduction in 11‐ketotestosterone was also observed in a study with male fathead minnow exposed to environmentally relevant concentrations of 17α‐ethinylestradiol for 21 d (Salierno and Kane ).…”
Section: Discussionmentioning
confidence: 99%